Analisis Beban Kerja Dan Kebutuhan Sumber Daya Manusia Dalam Aktivitas Bisnis Supplier Buah Dan Sayur Cahaya Buah Semarang 3 1,2 Menggunakan Metode Full Time Equivalent (FTE) - Sulistyowati, Endah; Lukiastuti, Fitri; Retnosary, Rieke (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to analyze workload and labor needs at Cahaya Buah Semarang, a fruit and vegetable supplier. Using a mixed method approach, this research combines qualitative methods through interviews and observations with quantitative methods using Full-Time Equivalent (FTE) to measureworkload. Data were collected from 10 informants, consisting of 2 women and 8 men, who work in distribution and packing. The analysis results show that both the distribution and packing teams are experiencing overload. The distribution team shows FTE values exceeding ideal capacity, with valuesof 2.28 for Armada 1 and 2.4 for Armada 2. Similarly, the packing team experiences overload in several categories, with FTE values ranging from 1.44 to 1.88. These findings underline the importance of effective human resource planning to address excessive workload and improve operational efficiency.The study provides recommendations for enhancing human resource management, including adjusting labor numbers and improving workforce planning strategies. Thus, it is expected to assist Cahaya Buah Semarang in addressing overload issues and improving productivity and service quality.